2011
DOI: 10.1097/prs.0b013e31822b6a82
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Nasal Dorsum in Rhinoplasty

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
13

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 85 publications
0
18
0
13
Order By: Relevance
“…Then as now, no comparative studies were identified that compare, for example, a sequential reduction with an en-bloc-reduction of the nasal dorsum [75]. While different retrospective case series describe the applied technique and the outcome, comparisons of different techniques are not possible.…”
Section: Types and Therapies Of Nasal Obstructionmentioning
confidence: 99%
See 3 more Smart Citations
“…Then as now, no comparative studies were identified that compare, for example, a sequential reduction with an en-bloc-reduction of the nasal dorsum [75]. While different retrospective case series describe the applied technique and the outcome, comparisons of different techniques are not possible.…”
Section: Types and Therapies Of Nasal Obstructionmentioning
confidence: 99%
“…While different retrospective case series describe the applied technique and the outcome, comparisons of different techniques are not possible. Although there is almost a consensus regarding augmentation of the nasal dorsum that autologous cartilage is the gold standard, there remains a considerable difference of opinion regarding the donor site and further treatment of the inserted cartilage [75]. Additionally, irradiated costal cartilage and bone transplants appear to be acceptable materials for augmentation of the nasal dorsum.…”
Section: Types and Therapies Of Nasal Obstructionmentioning
confidence: 99%
See 2 more Smart Citations
“…For nasal reconstruction the forehead is the gold standard due to the close colour match and subcutaneous thickness. The forearm skin flap can also be used if the forehead flap is unavailable [5, 6]. …”
Section: Introductionmentioning
confidence: 99%